Isolation of bacteria from Apis cerana hive, their antibacterial potency and cytotoxicity - YEKKI YASMIN; Lenni Fitri; FAUZIAH; FITRI WASLIYAH (Society for Indonesian Biodiversity, 2019)
Abstract. Yasmin Y, Fitri L, Fauziah, Wasliyah F. 2019. Isolation of bacteria from Apis cerana hive, their antibacterial potency and cytotoxicity. Biodiversitas 20: 2733-2738. This study aimed to identify bacteria from Apis cerana hive; to determine their antibacterial activity, and cytotoxic effect of hive extract as well as bacterial extract. Identification of bacteria isolated from the hive was carried out based on morphological and biochemical characters. The antibacterial assay of beehive bacteria isolates was done by disk diffusion method against Staphylococcus aureus and Escherichia coli. Toxicity test of beehive extract and beehive bacterial extract were carried out using Brine Shrimp Lethality Test (BSLT) with six final concentrations (32 ppm, 64 ppm, 126 ppm, 250 ppm, 500 ppm, and 1000 ppm). The LC50 value was determined by probit analysis using SPSS. Bacterial isolation showed there were four bacterial isolates from A. cerana hive were the genus Bacillus (BSL1, and BSL3), the genus Micrococcus (BSL2) and the genus Neisseria (BSL4). The antibacterial assay showed that BSL4 isolate has the highest antibacterial activity against S. aureus with the diameter of the inhibitory zone was 32.6 mm. Toxicity test showed that A. cerana hive extract and bacterial ethanol extract from A. cerana hive had LC50 value of 67,744 ppm and 86.985 ppm respectively and categorized as toxic.